If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 3y = o Solving -4x + 3y = o Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. -4x + 3y + -3y = o + -3y Combine like terms: 3y + -3y = 0 -4x + 0 = o + -3y -4x = o + -3y Divide each side by '-4'. x = -0.25o + 0.75y Simplifying x = -0.25o + 0.75y
| 2x-1-5x+3= | | 194=2-8(4+4p) | | 0=16t^2+32t+48 | | x^2+49x+14=42 | | 8(x-1)+9=5x+3(-1+x) | | 9x-11y=99 | | 14x^2+19=47 | | d^2-8d+144=145 | | 10x-6=9x+1 | | Y=.23x+.55 | | 343x^3= | | X^4-x^2=400 | | 3(4p+1)-2(p-5)= | | Y=.23+.55 | | X+.75x=140 | | x^2+169x+26=19 | | 4x^4+5x^2=8 | | x^2-10x-25=14 | | 8+3x-x=6 | | 21=w^2+4w | | 30=-x+100 | | (-3x-7)+(4x+7)=0 | | Tanx*cotx= | | 3x^2-4x+150=0 | | 2x*3x=10*(10x+10) | | 1/3x-15/120x= | | 0=2x^2+11x+21 | | -7(7x-3)+1=-49x+22 | | 22x-45=93 | | 0.75(2x-5)=0.50(x+2) | | 2x-4=3(x+6) | | X(x+3x)=8(8+(x+2)) |